DETERMINANTS OF INTENTION TO USE VILLAGE FUND INFORMATION SYSTEM - Widagdo, Ari Kuncara; Setyorini, Eka (UI Scholars Hub, 2018)
This study aims to examine factors that affect intention to use of village fund information system (SISKEUDES). Respondents in this research are village apparatus as operators of SISKEUDES. Data were collected using questionnaires. Sampling is conducted using the census sampling method, producing 212 respondents. This study uses the Structural Equation Model by using Partial Least Square (PLS) as a method of analysis. The result indicates that the quality of human resource and social factor influence the use of SISKEUDES. In addition, perceived system quality, perceived usefulness and perceived ease of use partially mediate the relationship between the quality of human resource and the intention to use SISKEUDES. In contrast, perceived information quality does not mediate the relationship between the quality of human resource and the intention to use of SISKEUDES.